Relationship between foreign direct investment and economic growth: A case of Romania - Farrukh Nawaz Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Inward Foreign Direct Investment (FDI) occupies a crucial and fundamental importance in the economic growth of any country. In this article we tried to gauge the impact of FDI upon economic growth of Romania. We extracted annual time series data for the dependent variable (GDP per capita growth) and explanatory variables (FDI, Gross Capital Formation and Employment) for the period spanning from 1993 to 2022. To determine the long run relationship between the variables, we used Auto regressive distributed lags (ARDL) bounds test of co-integration via EViews software. The empirical findings revealed the existence of a long-run relationship among the variables of the model. We found that FDI has a significant positive impact upon GDP; furthermore, FDI is also uni-directionally causing the Gross Capital Formation. These insights offer valuable implications for policymakers aiming to optimize the economic impact of FDI; it is recommended that Romania should focus on FDI-led growth policies so that economic growth could be further boosted.
Keywords: 330; Romania; FDI; economic growth; capital formation; employment; EasternEurope